The Relationship between Psychotropic Drug Use and Suicidal Behavior in Japan: Japanese Adverse Drug Event Report - Takeuchi, T.; Takenoshita, S.; Taka, F.; Nakao, M.; Nomura, K. (Pharmacopsychiatry, 2017)
Introduction: Very few studies have explored the adverse effect of psychotropic drugs worldwide.Methods: This study analyzed 1 813 suicide-related drug reports involving 553 patients collected from the Japanese National Adverse Drug Report Database between October 2001 and January 2012 to investigate psychotropic drugs associated with completed suicide vs. other suicide-related behaviors, including ideation and self-injury. The drugs investigated included antidepressants, antipsychotics, benzodiazepines, non-benzodiazepine hypnotic agents, noradrenergic and specific serotonergic antidepressants, selective serotonin reuptake inhibitors, serotonin and norepinephrine reuptake inhibitors, and other drugs.Results: These reports referenced 300 (54.2%) individuals who completed suicide. Adjusting for age, sex, and drugs used, the multivariate model revealed that participants who took antipsychotics were 1.70 times (95% CI, 1.11–2.61) more likely to complete suicide compared with those who did not. All other drugs became non-significant. Compared with those who took only one medication, those prescribed more than 4 drugs were more likely to complete suicide (OR 4.44, 95% CI, 2.40–8.20).Discussion: Antipsychotic drugs and polypharmacy may be regarded as predictors of completed suicide.
Keywords: adverse drug report database; polypharmacy; psychotropic drugs; completed suicide